Pengaruh Penguasaan Mata Kuliah Etika Bisnis Islam Terhadap Perilaku Konsumsi Mahasiswa - Lina Fatimatuzzahro; Lukman Santoso (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2019)
Purpose- This study aims to discuss (1) how the analysis of the influence of mastery of Islamic business ethics courses on consumption behavior of students of Islamic economics majors at IAIN Ponorogo (2) how the consumption behavior of students in Islamic economics is viewed from Islamic business ethics. Methods- The mix-method was used in this study. Data collection was carried out by distributing and interviewing students in the 6th semester of Islamic economics majors in class A, B, C and D with a total sample of 54 respondents and 3 speakers. Data analysis using simple linear regression analysis. Findings- Findings- The analysis shows that the mastery of Islamic business ethics has non significant effect on student consumption behavior. Secondly, student consumption behavior prioritizes consuming goods that are basic needs, goods that are lawful and good, goods that are simple, useful and not arbitrary (excessive) and tabdzir Research implications- This study is useful for understanding consumption behavior based on Islamic business ethics, especially for students. The implications of the study can be used as a basis for understanding consumer behavior in general, but are still limited to student objects so that further studies can develop a broader area of study.